Respiratory Infection and Otitis Media Visits in Relation to Pneumococcal Conjugate Vaccine Use in Saskatchewan - Ngoc-Hang Khuc; Ben Tan; Rosalie Tuchscherer; Nigel SB Rawson; Philippe De Wals (Canadian Journal of Infectious Diseases and Medical Microbiology)
BACKGROUND: In Saskatchewan, pneumococcal conjugate vaccination (PCV) was offered to high-risk children in 2002 and to all infants in 2005.